The retrovirus HTLV-1 inserts an ectopic CTCF-binding site into the human genome - Satou,Y; Miyazato,P; Ishihara,Y; Yaguchi,H; Melamed,A; Miura,M; Fukuda,A; Nosaka,K; Watanabe,T; Rowan,A; Nakao,M; Bangham,C (Proceedings of the National Academy of Sciences of the United States of America, 2016)
Human T-lymphotropic virus type 1 (HTLV-1) is a retrovirus thatcauses malignant and inflammatory diseases in 10% of infectedpeople. A typical host has between 104and 105clones of HTLV-1-infected T lymphocytes, each clone distinguished by the genomicintegration site of the single-copy HTLV-1 provirus. TheHBZgeneis constitutively expressed from the minus strand of the provirus,whereas plus-strand expression, required for viral propagation touninfected cells, is suppressed or intermittentin vivo, allowingescape from host immune surveillance. It remains unknown whatregulates this pattern of proviral transcription and latency. Herewe show that CTCF, a key regulator of chromatin structure andfunction, binds to the provirus at a sharp border in epigeneticmodifications in the pX region of the HTLV-1 provirus, in T cellsnaturally infected with HTLV-1. CTCF is a zinc-finger protein thatbinds to an insulator region in genomic DNA and plays a funda-mental role in controlling higher-order chromatin structure andgene expression in vertebrate cells. We show that CTCF boundto HTLV-1 acts as an enhancer blocker, regulates HTLV-1 mRNAsplicing, and forms long-distance interactions with flanking hostchromatin. CTCF binding sites have been propagated through-out the genome by transposons in certain primate lineages, butCTCF binding has not previously been described in present-dayexogenous retroviruses. The presence of an ectopic CTCF bindingsite introduced by the retrovirus in tens of thousands of genomiclocations has the potential to cause widespread abnormalities inhost cell chromatin structure and gene expression.